Rippability Assessment In Hilly Terrain Of Weathered Sedimentary Rock Mass - Nagendran, Sharan Kumar (Universiti Sains Malaysia, 2017)
Development in this country have forced structure to be constructed on the rock surface. Rock happened to cause dispute among geotechnical expert to analyse and make the right decision for the preliminary work and design. Rippability or ease of excavation in rock is of great concern in the preliminary work. Assessment can be made to rip the earth material with the use of seismic engineering method will be much more practical as well as low time consuming by spatially covering the site. The study area is at the proposed construction site for development of water reservoir and related infrastructure in Kampus Pauh Putra, Universiti Malaysia Perlis. The study focused on Seismic Refraction and Multichannel Analysis of Surface Wave (MASW) as the seismic velocity method which produce the shear wave velocity, Vs and compressional wave velocity, Vp distribution to provide a unique correlation and subsurface characterization. Conventional geotechnical method of using borehole was integrated with seismic velocity method to provide the appropriate assessment on rippability of the sedimentary rock. Correlated data can be used to categorize the machinery for the excavation activity based on the available systematic analysis procedure to predict the rippability of rock formation. Upper bound of the rippable and marginal velocity ranges from 1.8 km/s to 2.4 km/s and non-ripabble > 2.4 km/s based on the rippability chart. The available ripping machinery is D8 R, D9 R, D10 R, and D11 R for the excavation system based on the velocity chart. Ability of Caterpillar’s smallest ripper, D8R can successfully excavate the earth material based on its seismic velocity.